Characteristics and Antibacterial Activity of ZnO Nanoparticle Fortified Probiotic Yogurt - Erlita Sari, Pipit; Abidin, Zaenal; Arief, Irma Isnafia; Budiman, Cahyo (Buletin Peternakan, 2024)
Zinc deficiency is a major health issue in developing nations, especially in Southeast and South Asia. To address this, food fortification using nanotechnology, such as ZnO nanoparticles deemed safe by the US FDA, can enhance daily zinc intake essential for growth and immune health. This research emphasizes on yoghurt fortification with various types: ZnO nanoparticle fortification and the addition of probiotic bacteria Lactiplantibacillus plantarum subsp. plantarum IIA-1A5 (Accession Number: OR473281) and aims to analyze the nutritional value, characteristics, total lactic acid bacteria (LAB) and antibacterial activity of probiotic yogurt fortified with ZnO nanoparticles. There were six levels of treatment designed in this study and each treatment was tested three times. The statistical test used in analyzing the nutritional value, characteristics, total LAB and antibacterial activity in this study is the Tukey test which is applied as a multiple range test while in organoleptic testing using the Kruskal-Wallis non-parametric test. The results showed that the fortification of yogurt with ZnO nanoparticles had significant interaction (p<0.05) on yogurt viscosity, LAB content, and color attributes in hedonic quality test. The antibacterial activity towards Staphylococcus aureus and Escherichia coli produced by six treatments were moderate, with inhibition zones ranging between 5 to 10 mm. This study concluded that the fortified yoghurt treatment met the Indonesian National Standard (SNI), demonstrating the potential of this approach in addressing zinc deficiency in at-risk populations. This research underscores the promise of nanotechnology in food fortification strategies to combat micronutrient deficiencies globally